Charging powers of the electric vehicle fleet: Evolution and implications at commercial charging sites. (1st December 2021) - Simolin, Toni; Rauma, Kalle; Viri, Riku; Mäkinen, Johanna; Rautiainen, Antti; Järventausta, Pertti
Highlights: The charging powers of the current electric vehicle fleet are analyzed. Almost 80% of the electric vehicles support only around 4 kW charging powers. The development of the electric vehicle fleet during 2020–2040 is modelled. The energy requirement in commercial locations is predicted to increase by 134%. The peak of the normalized power is predicted to increase by 77%. Abstract: Electric vehicle (EV) charging is widely studied in the scientific literature. However, there seems to be a notable research gap regarding the charging power limitations of the on-board chargers of the EVs. In this paper, the present state of the maximum charging powers of the on-board chargers is thoroughly analysed using data from two commercial charging sites. Furthermore, the results of the analysis are used along with an EV fleet development model to form realistic future scenarios, which are then used for a simulation model that couples the charging sessions with measured charging profiles. The results of the simulations show that, due to the evolution of the EV fleet, the average energy consumption in commercial locations will increase by 134% on average from 5.6 to 8.7 kWh/EV to 13.0–19.6 kWh/EV during 2020–2040. Similarly, the peak of the normalized power increases by 77% on average from 1.1 to 1.4 kW/EV to 1.6–2.9 kW/EV. These values are essential to guide long-term decisions such as optimal sizing of charging infrastructure and parking policies.